If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6=15-2/3x
We move all terms to the left:
-6-(15-2/3x)=0
Domain of the equation: 3x)!=0We add all the numbers together, and all the variables
x!=0/1
x!=0
x∈R
-(-2/3x+15)-6=0
We get rid of parentheses
2/3x-15-6=0
We multiply all the terms by the denominator
-15*3x-6*3x+2=0
Wy multiply elements
-45x-18x+2=0
We add all the numbers together, and all the variables
-63x+2=0
We move all terms containing x to the left, all other terms to the right
-63x=-2
x=-2/-63
x=2/63
| -3(n-2)+6(n+3)=9-5(n-3)+8n) | | 8x+5-3x=2x+7 | | -17f+19f=2f | | 0.5(5-7t)=8-(4t+6) | | 1/2x+1/2x=1+x | | -7(x+7)=15 | | -9(6n-5)-3=-336 | | 13+19=-4(2x-8) | | 2x-17+8+2=x+20 | | -7x+10=-x+70 | | 2(5x-3)=3(3x-2)+x | | -(x)=9 | | U=-5u+6u | | 7x/4+48=13x/4 | | s11-s=24 | | x-5=-6x+58 | | 63=-1x | | -(-x)=-9 | | 7x/4+48=13x/44 | | -3=15-2/3x | | 2x+52=-x/6 | | 2=-8/b | | 18(x+12)=7 | | 7x+2=-5+5x+11 | | -20-4x=-6-16 | | 100x-10x=77.7-7.7 | | -10+9p=p+8p-10 | | 6+x+12=20 | | |4a+5|=|3a-2| | | x+1+2x+5=4x+2 | | f+82=84 | | -(-x)=9 |